Public Lecture: The Cinema Of Environmental Crisis - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2015)
(Posted on behalf of Dr. Anil Narine) There will be a public lecture about the implications of Eco-Trauma Cinema on Thursday, 29 Oct 2015, starting at 7:00 pm at the Djavad Mowafaghian World Art Centre, Goldcorp Centre for the Arts, 149 W. Hastings St. The event is co-presented by SFU’s Vancity Office of Community Engagement. Please see the full text for details.